Immunological reaction after facial hyaluronic acid injection. Issue 1 (1st January 2017) - Homsy, Antoine; Rüegg, Eva Meia; Jandus, Peter; Pittet-Cuénod, Brigitte; Modarressi, Ali
Abstract: We report two rare cases of inflammatory reactions with multiple subcutaneous facial painful collections after Hyaluronic acid injections, expose their management and discuss aetiologic hypothesis. Due to unfavourable evolution despite antibiotic treatment, surgical drainage was performed. Immune-mediated delayed hypersensitivity reactions were the most probable cause.